Everybody knows : Sammlung Dr. Hubert und Marie-Thérèse Peeters, Brügge. - Peeters, Hubert (Münster : Landesmuseum für Kunst und Kulturgeschichte, 1972)
Broodthaers, Marcel ; Segal, George ; Kaprow, Allan ; Rauschenberg, Robert ; Dine, Jim ; Rosenquist, James ; Oldenburg, Claes ; Englund, Lars Olov ; Wesselmann, Tom ; Krushenick, Nicholas ; Lichtenstein, Roy ; Warhol, Andy ; Salt, John ; Clarke, John Clem ; Woodburn, Stephen ; Mahaffey, Noel
Everybody knows : Sammlung Dr. Hubert und Marie-Thérèse Peeters, Brügge, Landesmuseum, Münster, 17.9.1972 - 22.10.1972
boek